2011
DOI: 10.1111/j.1365-2834.2010.01211.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical nurses in Magnet hospitals confirm productive, healthy unit work environments

Abstract: Implementation of structures that promote interdisciplinary and intradisciplinary collaboration and decision-making positively affect development of HWE. Gap analysis of the steps/components of the eight work processes/relationships essential to HWE may enable achievement of HWEs on all hospital clinical units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(99 citation statements)
references
References 27 publications
1
94
0
4
Order By: Relevance
“…Those findings were similar to the results of several published research studies that had examined the relationship between the years of experience and the level of work satisfaction. [33,36] CVNs with more years of experience in their units were exposed to different communication styles with other health care professionals. Another study also supported this finding and concluded that nurses with more than 30 years of experience had higher levels of satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Those findings were similar to the results of several published research studies that had examined the relationship between the years of experience and the level of work satisfaction. [33,36] CVNs with more years of experience in their units were exposed to different communication styles with other health care professionals. Another study also supported this finding and concluded that nurses with more than 30 years of experience had higher levels of satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…In congruence with this, Abdullah [34] stated that Magnet hospitals allow opportunities for nursing staff to participate in the hospital' activities, focus on the nurse managers' abilities, and the coefficient relationship between the physicians and nurses. Moreover, Kramer and Schmalenberg [35] studied the factors which the nursing staff considered it as important for being able to provide high quality care, stated that these factors includes, sharing the work with competent nurse, professional nurse-physician relationship, effective communication, autonomy and accountability of nurses, empowerment of nurse manager/supervisor, control over nursing practice and work environment, educational opportunities, effective staffing, and concern for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…The world in which public managers function is rapidly changing, indicating a shift towards more decentralization at organizational levels, while promoting and are ahead of care are able to make decisions, to achieve collective participation in the production of quality care to patients, and allow a more participatory management (6)(7) .…”
Section: Participativa En Un Hospital Públicomentioning
confidence: 99%
“…Nurses who are visionary leaders and are ahead of care are able to make decisions, to achieve collective participation in the production of quality care to patients, and allow a more participatory management (6)(7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation